2023
DOI: 10.3390/jfb14020102
|View full text |Cite
|
Sign up to set email alerts
|

The Fluoride Ion Release from Ion-Releasing Dental Materials after Surface Loading by Topical Treatment with Sodium Fluoride Gel

Abstract: The study aimed to investigate the rechargeability of ion-releasing dental material specimens immersed in distilled water for 25 months, which depleted their ion-releasing ability. Four restorative dental materials (alkasite composite, giomer, glass-ionomer, and composite material) presented with 24 specimens were studied after topical treatment with a concentrated fluoride gel. The effect of resin coating on the ion uptake and release was investigated on additional 42 specimens of restorative dental materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Wang et al examined the effects of coating on initial F release from resinmodified GIC 49) . Furthermore, Kelić et al reported that the presence of a dental adhesive system or GIC coating significantly reduced the recharge capacity compared to uncoated materials 50) . In contrast to previous findings, Tay et al proposed that adhesives could act as permeable membranes and aid in remineralizing tooth structure, halting the caries process 51) .…”
Section: Qualitative Study and Outcome Measuresmentioning
confidence: 99%
“…Similarly, Wang et al examined the effects of coating on initial F release from resinmodified GIC 49) . Furthermore, Kelić et al reported that the presence of a dental adhesive system or GIC coating significantly reduced the recharge capacity compared to uncoated materials 50) . In contrast to previous findings, Tay et al proposed that adhesives could act as permeable membranes and aid in remineralizing tooth structure, halting the caries process 51) .…”
Section: Qualitative Study and Outcome Measuresmentioning
confidence: 99%